Penerapan Konsep Peringkat Risiko pada Manajemen Risiko Hukum di Perbankan Syariah - Siti Kadariah; Anriza Witi Nasution; Saparuddin Siregar (Jurnal EMT KITA, 2023)
This study aims to look at the risk rating, the risk rating is the final conclusion on the Bank's risk after considering the mitigation carried out through the implementation of risk management, to determine the bank's risk rating refers to the rating matrix. This matrix basically maps out risk ratings resulting from a combination of inherent risk and quality of risk management implementation. Research results determine the risk rating because the determination of the rating assessment is the basis for banks to categorize bank risk ratings. The results of applying risk ratings for banks are categorized into five ratings, namely, Low to moderate, Moderate, Moderate to high High, Low.